Parental smoking behavior and caries experience in preschool children - Leroy R, Hoppenbrouwers K, Jara A, Declerck D. (Journal compilation, 2008)
The study aimed to explore the association between parental smoking behavior and caries experience in young children, taking into account the socioeconomic status and oral health-related behavior